Investigation of Ethnic Diversity In Pakistan: A Case Study of Karachi - Farhat Niazi ,; Azra Parveen Azad, (Journal of Basic & Applied Sciences, 2018)
In developing countries increasing population and lack of good governance are the major issues and Pakistan is no exception. These issues are highlighted most in the context of urban centers. Karachi is the most populous city of Pakistan and currently ranked 6th among the mega cities of the world. After partition this city has grown up rapidly due to influx of both national and international immigrants. Urdu speaking persons are the largest ethnic group in Karachi and Pashtuns are second largest group who came to Karachi. It can’t be wrong to say that there are even more Pashtuns in Karachi than in Peshawar itself. Almost 50% of the total population is Urdu speaking whereas 25% of total population is Pashtun in Karachi, whereas, 14% are from Punjab and remaining 9% speaking other languages are settled here. Similarly there are areas in the city marked for Christians, Hindus, Parsis etc. Census Data for the years 1951, 1961, 1972, 1981 and 1998 are taken to analyze the variability of Religion, Population and Language (language data is not available for 1972 census). Spatial development of Slums / Katchi-Abadi 1988 and projection for 2000 has also been discussed. The change in population for the years 1981 and 1988 has been mapped using GIS. MP & ECD Analysis Zones have been used and according to the findings during the years 1986-2000 population increase percent is higher in Surjani Town and Taisar Town. It is also concluded that 96% population living in the city are Muslims and speak more than 9 different languages.